2020
DOI: 10.1002/cjoc.202000456
|View full text |Cite
|
Sign up to set email alerts
|

Sarcaglarols A—D, Lindenane−Monoterpene Heterodimers from Sarcandra glabra Based on Molecular Networks

Abstract: Sarcandra glabra | Molecular networks | Natural products | Structural elucidation | Peroxides Sarcaglarols AD (1-4), two pairs of lindenane−monoterpene heterodimers fused by a 1,2-dioxane moiety, were discovered and isolated from the leaves of Sarcandra glabra guided by MS/MS molecular networking-based strategy. Their planar structures, absolute configurations of basic skeleton and flexible polyhydric side chain were established by analysis of HRESIMS, NMR spectroscopic data, ECD spectrum, and the X-ray diffra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…All dimers were tested for their inhibitory activity on fat deposition in free fatty acid (FFA)-exposed L02 cells based on the hepatoprotective and hypolipidemic effects of the S. glabra . ,, Compounds 1 and 2 could significantly attenuate lipid deposition in L02 cells at a concentration of 10 μM, as visualized by Bodipy staining (Figure ). The free hydroxyl groups seem to enhance the inhibitory activity of the compounds against lipid accumulation.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All dimers were tested for their inhibitory activity on fat deposition in free fatty acid (FFA)-exposed L02 cells based on the hepatoprotective and hypolipidemic effects of the S. glabra . ,, Compounds 1 and 2 could significantly attenuate lipid deposition in L02 cells at a concentration of 10 μM, as visualized by Bodipy staining (Figure ). The free hydroxyl groups seem to enhance the inhibitory activity of the compounds against lipid accumulation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Nakai, which is widely distributed in southern Asia, is one of the renowned traditional Chinese medicines and is used as an anti-inflammatory and an adjuvant treatment for cancer . Modern pharmacological studies have shown that some of the components in S. glabra exhibit positive hepatoprotective and hypolipidemic effects. , Based on our previous research on sesquiterpenes from the Chloranthaceae plants, , a chemical investigation of the roots of S. glabra was carried out. As a result, five unprecedented norlindenane sesquiterpene dimers, sarglaromatics A–E ( 1 – 5 , respectively), were isolated (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous phytochemical researches on the LDS oligomers from Chloranthaceae plants, several kinds of novel dimeric and trimeric oligomers have been discovered. [ 3,7,10‐13 ] According to their interesting biogenetic pathway, it is worthwhile and expectable to explore naturally‐occurring unique polymeric skeletons based on LDS units. Thus, Chloranthus henryi , a famous medicinal plant for the treatment of traumatic injuries, rheumatic arthralgia, fractures, pulmonary tuberculosis, and neurasthenia in southwestern China, [ 14 ] was selected as our research objective to discover novel LDS oligomers.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…7,11 carbon signals indicated that a new ring was formed in 2. The obvious downfield shift of C-6 (Δδ C + 10.9), C-8 (Δδ C + 5.8), and C-6′ (Δδ C + 12.1) along with oxygenated C-7 (δ C 87.2) suggested that the C-6′−O−C-7 linkage in 2 was formed…”
mentioning
confidence: 99%